CMOS Based Dual Band Radio Frequency Rectifier for Energy Harvester - Muhd Hafizuddin Abd Rahman; Mat Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2024)
This paper proposed a dual-band rectifier for RF energy harvesting based on the CMOS architecture which is designed to operate at 900 MHz and 2.4 GHz using Cadence EDA tools with 45 nm CMOS technology. The multi-band cross-coupled rectifier designed with 5 stages at 900 MHz and 5 stages at 2.4 GHz. The load resistance of 100 KΩ is connected at 900 MHz rectifier and 2.4 GHz rectifier to measure the output voltage above 1 V and verify the functionally of multi-stage cross-coupled rectifier circuit. The greatest efficiency that the 900 MHz rectifier can achieve is 35% when the output voltage is 4.64 V and the input power is 10 dBm. On the other hand, the 2.4 GHz rectifier can attain a maximum efficiency of 36% and 4.7 V of the output voltage at 10 dBm of input power. Last but not least, the cross-coupled rectifier circuit is designed with a layout size of 53.24 nm2. In summary, it is possible to construct the suggested CMOS dual band rectifier circuit in a low voltage application.